NILAI BUDAYA DAN POLA PEWARISAN SASTRA LISAN DI SULAWESI TENGGARA: PENDEKATAN TRADISI LISAN - Salniwati Salniwati; Nurtikawati Nurtikawati (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This study examines the cultural values and patterns of inheritance of oral literature on Ethnics in Southeast Sulawesi by the oral tradition approach. This research data consists of secondary data and primary data with interview and recording collecting technique. Data were analyzed by using qualitative descriptive method. The results of this study indicate that the cultural value of oral literature has a diversity of points of view on ethnic groups in Southeast Sulawesi. Oral literature is assessed as a religious system, spirit, aesthetics, ethics, morals, entertainment and education. Cultural values are actualized in the way of life and become the signs of character formation of society. The pattern of inheritance of oral literature is a form of product and process of oral tradition. As a product, the arrival or form of oral oral literary messages from person to person across generations. As for the process, oral literature is transmitted through mouth to mouth along with mnemonics devices. This transmission process is influenced by place, time, media or means, performer, situation, mood and method.